Mitogen-activated protein kinase kinase 6 is involved in the immune response to bacterial di-/tripeptide challenge in grass carp Ctenopharyngodon idella. Issue 84 (January 2019) - Qu, Fufa; Tang, Jianzhou; Liao, Jinting; Chen, Bei; Song, Peng; Luo, Wenjie; Xiong, Ding; Liu, Tianting; Gao, Qianting; Lu, Shuangqing; Liu, Zhen
Abstract: Mitogen-activated protein kinase kinase 6 (MKK6) is an essential component of the p38MAPK signaling pathway, which is involved in the modulation of inflammation, cell apoptosis and survival responses in mammals. However, the function of MKK6s in teleosts is still unclear. In this study, a fish MKK6 homolog ( Ci MKK6) was first identified from the grass carp ( Ctenopharyngodon idella ), a freshwater fish. Ci MKK6 cDNA encodes a putative protein of 357 amino acids that contains conserved structural characteristics of the MKK6 family, including the S_TKc domain, SVAKT motif and DVD site. The deduced Ci MKK6 protein exhibits high sequence homology with other reported fish MKK6s and shares the closest relationship with MKK6 from Danio rerio . Quantitative real-time PCR (qRT-PCR) analysis revealed that Ci MKK6 mRNA was widely expressed in all tested tissues and stages of embryonic development. Additionally, the transcript levels of Ci MKK6 in the intestine were significantly upregulated in response to bacterial muramyl dipeptide (MDP) and L-Ala-γ-D-Glu-meso-diaminopimelic acid (Tri-DAP) stimulation. Moreover, subcellular localization analysis indicated that Ci MKK6 was distributed in both the cytoplasm and the nucleus of HEK293T cells. Finally, overexpression of Ci MKK6 significantly enhanced the transcriptional activity of the AP-1 reporter gene in HEK293T cells. Overall, these findings may help better clarify the immune function of teleost MKK6s and provide new insight into the immune defense mechanisms of grass carp. Highlights: The cDNA sequence of Ci MKK6 was first identified from Ctenopharyngodon idella. Ci MKK6 transcript was ubiquitously expressed in all tested tissues and developmental stages. Ci MKK6 mRNA levels could be upregulated significantly by bacterial MDP and Tri-DAP challenge. Ci MKK6 was dispersedly present in the cytoplasm and nuclear areas of HEK293T cells. Ci MKK6 was an efficient regulator of AP-1 signaling pathway in HEK293T cells.